A review of characteristic study of micro calcification using son mammogram images - R. Jothilakshmi, G; Arun Raaza, Dr; Y. Sreenivasa Varma, Dr; V. Rajendran, Dr; Guru Nirmal Raj, R (International Journal of Engineering and Technology, 2018)
In recent years, the mortality rate in women increases a lot due to occurrence of breast cancer. The challenging task in medical field is to find breast cancer at an early stage. Because the detection of breast cancer at its early stage makes the treatments easy and increases the survival rate of victim. In this review paper, a detailed explanation is given about the characteristics of micro calcification (ie its shape and distribu-tion) and detailed literature survey is done that shows the techniques used previously to detect the Micro calcification from different diag-nostic sources. Moreover, this review paper proposes a new algorithm, to detect micro calcification and to find its classification (benign or malignant) from sono mammogram images at an early stage. First filtering will be taken place in order to enhance the image. Second the image is to be binned and the affected area is to be separated (ROI) by edge detection. Then the size, shape, distribution and density of the ROI will be determined. From the characteristics of RoI, a mathematical model will be developed and signatures to be found to confirm the occurrence of micro calcification and to find its classifications.Â Â Â